The effects of type and severity of illegal sexual harassment and organizational justice on the reactions of females, human resource professionals, and employment lawyers to harassment situations in the workplace - Frame, Jennifer Hames, author; Thornton, George C., III, advisor; Cropanzano, Russell, committee member; Hogler, Raymond L., committee member; Bloom, Larry J., committee member (Colorado State University. Libraries, 2000)
The present study used a legal framework to examine the effects of type (hostile environment vs. quid pro quo) and severity (mild vs. severe) of sexual harassment as well as level of organizational justice during the harassment complaint process on the reactions of females, lawyers, and human resource professionals (HR) to written depictions of sexual harassment in the workplace. Females and HR's knowledge of sexual harassment law was examined and it was found that although HR had more legal knowledge than females, both groups had some key knowledge deficiencies (e.g., knowledge of legal liability guidelines and administrative issues). Females' reactions to harassment varied depending on the type and level of harassment such that females were more likely to say they would pursue and/or win a legal case for quid pro quo and severe scenarios than for hostile environment and mild scenarios. In quid pro quo scenarios (vs. hostile environment), lawyers were more likely to say they would recommend a victim pursue legal action and were more likely to believe the victim would win a court case. All subjects had more negative reactions to harassment when organizational justice (i.e., perceived fairness of company procedures and interpersonal treatment) was lacking in the complaint process. When justice was absent, females were more likely to indicate they would pursue a lawsuit or quit the job instead of filing an internal complaint. Lawyers were more likely to recommend victims pursue internal action (vs. a lawsuit) when justice was present and felt that a plaintiff was more likely to win a court case when justice was absent. HR professionals recognized that adhering to principles of organizational justice could help a company avoid legal liability. Overall, the subject groups tended to agree about potential reactions to harassment, though the magnitude of the predicted responses varied in some cases. Implications of the findings on sexual harassment prevention training and education and on design of complaint systems are discussed in terms of the principles of organizational justice as related to the affirmative defense described in Burlington Industries, Inc. v. Ellerth and Faragher v. City of Boca Raton (1998).
Keywords: criminology; law; women's studies